Zum Verhältnis von Deutschunterricht und Erstsprachenunterricht bei migrationsgesellschaftlicher Mehrsprachigkeit im schultheoretischen Kontext - Hawlik, Rainer (Revija za elementarno izobraževanje, 2024)
With reference to the power-critical research of migration pedagogy, this contribution of non-empirical research theoretically discusses the conditions under which numerous school-age multilingual children with German as a Second Language (GSL) pursue their education in the Austrian school system. From a systems theory perspective, the article focuses on the attitudes of teacher candidates towards their largely multilingual student body in Vienna and raises questions about the habitualization of German as a target language and the barriers to the education of multilingual students, who often come from socio-economically and culturally disadvantaged backgrounds in Vienna.